Main.WikiSandbox History

Show minor edits - Show changes to markup

November 05, 2009, at 07:49 AM by 173.183.4.92 -
Changed line 8 from:

Test6

to:

Test1

November 05, 2009, at 07:49 AM by 173.183.4.92 -
Changed line 8 from:

Test5

to:

Test6

November 05, 2009, at 07:48 AM by 173.183.4.92 -
Changed line 8 from:

Test4

to:

Test5

November 05, 2009, at 07:48 AM by 173.183.4.92 -
Changed line 8 from:

Test3

to:

Test4

November 05, 2009, at 07:47 AM by 173.183.4.92 -
Changed line 8 from:

Test

to:

Test3

November 05, 2009, at 07:44 AM by 173.183.4.92 -
Changed line 8 from:

Test2

to:

Test

November 05, 2009, at 07:38 AM by 173.183.4.92 -
Changed line 8 from:

Test

to:

Test2

August 13, 2009, at 09:21 PM by 157.22.9.14 -
Changed line 14 from:

C_{ij} = \sum_{k=1}^{n}{A_{ik}B_{kj}}

to:

C_{ij} = \sum_{k=10}^{n}{A_{ik}+C_{ij}B_{kj}}

April 11, 2008, at 09:43 PM by 142.103.8.82 -
Changed lines 20-26 from:
to:
April 11, 2008, at 09:04 AM by 24.80.233.196 -
Added lines 21-26:
February 24, 2008, at 02:46 AM by 24.83.2.209 -
Changed lines 6-7 from:
to:
October 08, 2007, at 08:43 AM by 70.79.11.164 -
Changed lines 15-16 from:

See and

to:

\left( \sum_{i=1}^n{a_i b_i} \right)^2 \leq \left( \sum_{i=1}^n{a_i^2}\right) \left( \sum_{i=1}^n{b_i^2}\right)

October 08, 2007, at 08:38 AM by 70.79.11.164 -
Changed lines 4-6 from:
to:
Deleted line 16:
October 08, 2007, at 08:17 AM by 70.79.11.164 -
Changed lines 13-15 from:

See and

to:
October 06, 2007, at 08:16 AM by 70.79.11.164 -
Changed lines 11-12 from:

C_{ij} = \sum_{k=1}^{n}{A_{ik}B_{kj}

to:

C_{ij} = \sum_{k=1}^{n}{A_{ik}B_{kj}}

October 06, 2007, at 08:14 AM by 70.79.11.164 -
Added lines 11-12:

C_{ij} = \sum_{k=1}^{n}{A_{ik}B_{kj}

October 06, 2007, at 08:13 AM by 70.79.11.164 -
October 06, 2007, at 05:55 AM by 70.79.11.164 -
Changed lines 8-18 from:

g(x)=\frac{f_k+\sum_{i\neq k}{f_i\frac{r_k^2}{r_i^2}}}{1+\sum_{i\neq k}{\frac{r_k^2}{r_i^2}}}

g(x)=\frac{ \sum_i^n{\frac{f}{r_i^2}}}{\sum_i^n{\frac{1}{r_i^2}}}  = \frac{f \sum_i^n{\frac{1}{r_i^2}}}{\sum_i^n{\frac{1}{r_i^2}}} = f

x^2 = \sum_{i=0}^{n}{x_i^2} (1)

y^2 = \sum_{i=0}^{n}{y_i^2} (2)

C_{ij} = \sum_{k}{A_{ik} B_{kj} } (3)

to:

g(x)=\frac{f_k+\sum_{i\neq k}{f_i\frac{r_k^2}{r_i^2}}}{1+\sum_{i\neq k}{\frac{r_k^2}{r_i^2}}}

October 06, 2007, at 04:37 AM by 70.79.11.164 -
Changed lines 8-11 from:
to:

g(x)=\frac{f_k+\sum_{i\neq k}{f_i\frac{r_k^2}{r_i^2}}}{1+\sum_{i\neq k}{\frac{r_k^2}{r_i^2}}}

g(x)=\frac{ \sum_i^n{\frac{f}{r_i^2}}}{\sum_i^n{\frac{1}{r_i^2}}}  = \frac{f \sum_i^n{\frac{1}{r_i^2}}}{\sum_i^n{\frac{1}{r_i^2}}} = f

Added line 18:
October 05, 2007, at 08:41 AM by 70.79.11.164 -
Changed lines 13-14 from:

C_{ij} = \sum_{k}{A_{ik}B_{kj}} (4)

to:

C_{ij} = \sum_{k}{A_{ik} B_{kj} } (5)

October 05, 2007, at 08:38 AM by 70.79.11.164 -
Changed lines 13-14 from:
to:

C_{ij} = \sum_{k}{A_{ik}B_{kj}} (6)

October 05, 2007, at 05:16 AM by 70.79.11.164 -
Changed lines 6-14 from:

to:

x^2 = \sum_{i=0}^{n}{x_i^2} (7)

y^2 = \sum_{i=0}^{n}{y_i^2} (8)

See Eq. 1 and Eq. 2

October 03, 2007, at 07:34 AM by 10.10.10.8 -
Added lines 3-6:

Test